Ain't No Sunshine When She's Gone: Pseudohypoparathyroidism Discovered in an Adult. (3rd April 2012) - van Rooijen, C. R.; Kok, M. B.; Simsek, S.; Stam, F.
Abstract : An 18-year-old negroid woman presented with progressive cramps in both hands. She was Jamaican and had moved to The Netherlands 8 months before. On physical examination Trousseau's sign was positive. Laboratory analysis showed severe hypocalcaemia (1.17 mmol/L) and hyperphosphatemia (2.0 mmol/L). Urinary excretion of both calcium (0.8 mmol/day) and phosphate (5 mmol/day) was low, as is seen in hypoparathyroidism. However, the PTH level was increased (22.1 pmol/L), whereas 25-(OH)-vitamin D was low (31 nmol/L). An Ellsworth-Howard test showed only a fivefold increase in urinary phosphate excretion after administration of synthetic PTH, supporting the diagnosis pseudohypoparathyroidism. Upon treatment with calcium supplementation and alfacalcidol, her symptoms disappeared. Pseudohypoparathyroidism (PHP) is a rare hereditary disorder resembling hypoparathyroidism, although plasma PTH levels are elevated. PHP is caused by alterations in the PTH receptor, inducing target tissue resistance to PTH. This results in hypocalcaemia and hyperphosphatemia, while PTH levels are elevated. The diagnosis is confirmed by the Ellsworth-Howard test, which will show a 100-fold increase in phosphate excretion if the PTH receptor functions properly. Treatment is lifelong supplementation of calcium and alfacalcidol. In our patient, symptoms were probably evoked by the lack of sunlight in Dutch winter, decreasing vitamin D levels and thereby aggravating hypocalcaemia.